Efficacy of cognitive behavioral therapy for insomnia in breast cancer: A meta-analysis. (February 2021) - Ma, Yan; Hall, Daniel L.; Ngo, Long H.; Liu, Qingqing; Bain, Paul A.; Yeh, Gloria Y.
Summary: Insomnia is highly prevalent among patients with breast cancer (BC). Although cognitive behavioral therapy for insomnia (CBT-I) is available in integrative oncology settings, it poses unique challenges for BC survivors. Our review aimed to assess the evidence for the therapeutic effects of CBT-I on insomnia in BC. Randomized controlled trials (RCTs) that included patients/survivors with BC and insomnia, and at least one validated self-report measure of sleep quality were included in the review. Of the 14 included RCTs (total N = 1363), the most common components incorporated in CBT-I interventions were sleep hygiene, stimulus control and sleep restriction. Pooled effect sizes favored CBT-I at post-intervention (Hedges' g = −0.779, 95% CI = −0.949, −0.609), short-term follow-up (within six months, Hedges' g = −0.653, 95% CI = −0.808, −0.498), and long-term follow-up (12 mo, Hedges' g = −0.335, 95% CI = −0.532, −0.139). In sub-analyses, CBT-I had similar effect sizes regardless of potential modifiers (comparison design, delivery formats, etc.). As an integrative oncology intervention, CBT-I is efficacious for reducing insomnia and improving sleep quality in women treated for BC, with medium-to-large effect sizes that persist after intervention delivery ends. Given the variability in the CBT-I components tested in RCTs, future studies should investigate the optimal integration of CBT-I components for managing insomnia during BC survivorship.